Cerebral Palsy and Rhizotomy: A ten year follow-up study with Gait Analysis - Subramanian, Nivedita (Department of Human Biology, 2017)
In 1985, a cohort of 14 children with cerebral palsy underwent a neurosurgical procedure - selective posterior rhizotomy - in an effort to reduce their spasticity. They were part of a prospective study in which their gait was analysed before surgery and at one and three years' post-operatively. In 1995, ten years after surgery, there were important questions that needed to be addressed: would their gait be different from the findings before surgery and three years after surgery and how would they compare with age-matched normal subjects? Three of the original subjects were lost to follow-up and 11 were invited to participate in this long-term study. Their ages ranged from 12 to 24 years at this time of evaluation. Their gait was studied in the sagittal plane by taping retro-reflective markers onto the greater trochanter, lateral femoral epicondyle and lateral malleolus and having the subjects walk in a direction perpendicular to a video camera recording their gait. The data were digitised and analysed making use of custom written software and all relevant gait parameters were calculated. The parameters evaluated were the ranges of motion and midrange values of the knee and thigh, and the spatial-temporal parameters, namely cadence, stride length and velocity. Data were also obtained from twelve age-matched normal control subjects. The ten-year results were compared to the pre-operative data, the data obtained from the three-year study and the normal controls. A statistical analysis was performed on these parameters by using multiple analysis of variance (MANOVA) and post hoc comparisons were performed with a Scheffe test and a significance level set at p < 0.05. Results indicated that after ten years, the joint ranges of motion and mid-range values did not differ significantly from the normal values. The values also did not vary significantly from the values obtained in the three-year follow-up study, suggesting that functional changes acquired due to rhizotomy were of long term duration. The spatial-temporal parameters, however, did differ significantly from the normal range. Although this finding may have been influenced by the environment and subject motivation, the reduced cadence and stride length meant that the cerebral palsy subjects walked slower than their normal counterparts. This project, while confirming the results of the previous subjective studies, provides the first long-term objective data that establishes the effectiveness of selective posterior rhizotomy in improving and maintaining locomotor function for children with spastic cerebral palsy.